Developing control algorithms for electrical starter generator using DSP and validating using hardware prototype - Toh, Tai Meng. (2012)
Permanent Magnet Synchronous Machines (PMSM) is extensively utilized in various industries and applications. Traditionally analogue technology has been employed to provide PMSM speed and excitation control however by employing digital technology, much improved PMSM control can be achieved This report presents a detailed model of the PMSM in MatLab/Simulink with a closed-loop control system consisting of a PI control to regulate the current and the speed of the PMSM. A Digital Signal Processor (DSP) is used to perform simulation to validate the performance of the PMSM prior to the hardware simulation. Current sensor, voltage sensor and speed encoder are used in this project. The speed of PMSM is used as an outer loop control and the current reading of the PMSM is used as inner loop control. This report also demonstrates the hardware implementation between the Digital Signal Processor and Permanent Magnet Synchronous Machine.